Estimation of Probable Maximum Precipitation for Planning of Soil and Water Conservation Structures - Dilip G. Durbude (Journal of Soil and Water Conservation, 2022)
The Southern part of Banswara district of Rajasthan state is mostly dominated by tribal populations, the socio-economic conditions of the tribals are pathetic by all standards. Even though the average rainfall is very good, the region is always under influence of drought. This mainly due to the lack of management, inadequate knowledge and inadvertence of water conservation practices. Hence, it is the necessary to plan the watershed development activities to conserve the available resources and further enhance the land productivity. Therefore, in the present study, the effort has been made to estimate the maximum one day rainfall for different return periods which can be used for design of various conservation structures in the area. The Hershfield technique and Gumbel’s theory of extreme values were used for estimation of maximum one day rainfall. The highest one day probable maximum precipitation (PMP) for the area is found as 350.14 mm. The ratio of maximum one day rainfall for 100 year return period to the maximum one day observed rainfall is found as 1.05. The maximum one day rainfall for different return periods were also estimated, which can be used for the design of overflow arrangement of conservation structures.